2018
DOI: 10.1002/jso.25260
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term outcomes of pleurectomy decortication and extrapleural pneumonectomy in mesothelioma

Abstract: Background/Objectives We evaluated postoperative mortality and complications after extrapleural pneumonectomy (EPP) and pleurectomy decortication (P/D) to better understand their effectiveness in malignant pleural mesothelioma (MPM). Methods A meta‐analysis was done to evaluate 30‐day mortality and postoperative complications. In addition, in‐patients data of 500 eligible patients with MPM who underwent EPP or P/D was extracted from the New York Statewide Planning and Research Cooperative System (SPARCS). Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 38 publications
2
25
1
Order By: Relevance
“…reported to be constant in the setting of multimodality therapy. [9][10][11] Allen et al reported 46.1% of radiotherapyrelated deaths in patients who received IMRT after EPP, with a V20 limited to 20% and a mean lung dose (MLD) of 15 Gy. 12 Moreover, in a multicenter phase 2 study trial, postoperative hemithoracic high-dose radiotherapy in the context of trimodality therapy failed to significantly improve locoregional relapse-free survival compared with no further treatment after EPP.…”
Section: Discussionmentioning
confidence: 99%
“…reported to be constant in the setting of multimodality therapy. [9][10][11] Allen et al reported 46.1% of radiotherapyrelated deaths in patients who received IMRT after EPP, with a V20 limited to 20% and a mean lung dose (MLD) of 15 Gy. 12 Moreover, in a multicenter phase 2 study trial, postoperative hemithoracic high-dose radiotherapy in the context of trimodality therapy failed to significantly improve locoregional relapse-free survival compared with no further treatment after EPP.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-two percent of surveyed surgeons routinely performing MPM procedures agreed that P/D should be defined as resection of the visceral and parietal pleura, and the authors coined the term "extended P/D" to refer to P/D additionally involving resection of the pericardium or diaphragm and dissection of the pleural surfaces along the interlobar fissures extending to the hila to facilitate maximal cytoreduction. 64 While EPP and P/D each offers its own distinct advantages and disadvantages and a considerable amount of controversy exists regarding the preferred surgical approach, [65][66][67][68][69][70][71][72][73] the goal of each procedure is to achieve maximal cytoreduction via macroscopic complete resection (MCR), defined as <1 cm of residual tumor after resection. Selection of patients for surgical intervention is critical as the ideal candidates would have early-stage, less bulky disease and favorable prognostic signs (i.e., good performance status, epithelial histology); however, as mentioned previously, staging of MPM can be very challenging and more extensive disease can be found on exploratory thoracoscopy.…”
Section: Surgical Managementmentioning
confidence: 99%
“…The review concluded that P/D may provide a safer option when possible for MPM patients. 73 To date, no studies have compared EPP and P/D outcomes in a randomized fashion with quantitative measurement of disease volume to normalize pathologic disease stage.…”
Section: Surgical Managementmentioning
confidence: 99%
“…The identification of risk factors associated with mesothelioma may prevent patients from gone into the high danger of disease. The comorbidities associated with malignant mesothelioma are cardiovascular diseases [63],cancer-related emotional distress [64], pulmonary, neurologic, diabetes, anemia, psychiatric disorders, hypothyroidism, metastatic cancer, weight loss, and electrolyte disorders [65]. V. Conclusion Epidemiology of diseases at early stages assumes as a substantial measure for patient's appropriate treatment.…”
Section: IVmentioning
confidence: 99%